An Adaptive Virtual Reality-Based Serious Game for Therapeutic Rehabilitation - Ferreira, Bruno; Menezes, Paulo (International Journal of Online and Biomedical Engineering (iJOE), 2020)
Conventional motor rehabilitation therapies followed by stroke survivors during their recovery process, are typically intense and involve numerous repetitions of task-specific recommended exercises. However, due to the lack of short-term or immediate results, patients tend to lose motivation on the rehabilitation process, and on performing the therapist recommended exercises at home between sessions. The work described in this article proposes to engage the patients with the therapeutic exercises by transforming the latter into specially designed serious games. After an initial evaluation by therapists, a pilot study was conducted on a rehabilitation clinic that showed that this system is adequate for about 75% of the clinical cases treated. The proposed game was globally well-accepted by patients, showing to be motivational and engaging. These promising results lead us to believe that immersive-based games can indeed be a valuable aid for motor rehabilitation therapies.